Determinants of the Amount of Waste in East Java - Joko Ade Nursiyono; Chotimah, Chusnul; Fitrianti , Warisna Endah (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Listed as one of the largest waste contributor provinces in Indonesia. The population of East Java in 2020 reached 39 million people, it is the second highest in Indonesia. The increasing number of people accompanied by an increase in income will increase people's consumption in an area and this will cause the increasing amount of waste. If this waste problem is not handled properly, it will have a domino effect as well as degrading the environment. This study wanted to determine the effect of population, real expenditure per capita per year and the number of waste banks on the amount of waste in 2020 in East Java Province. This study uses a comparison of OLS Regression and Robust Regression models. The criteria for selecting the best model use the smallest MAPE, RMSE, and RSE values and the largest R-square value. The results of the partial test and the simultaneous test show that the variables of population, real expenditure per capita per year and the number of waste banks significantly affect the variable amount of waste in East Java with the selected model is the Robust Regression model. The R-square value of the Robust Regression model in this study is 0.8909, meaning that the model's ability to explain the variability of the East Java waste amount data is 89.09 percent, and the rest is explained by other variables not included in the model.